DESIGN OF GROUNDING GRID WITH AND WITHOUT GROUNDING ROD IN TWO-LAYER SOIL MODEL VIA GENETIC ALGORITHMS - Gursu, Baris; Ince, Melih Cevdet (Yildiz Technical Univ, 2008)
Limiting Grounding Potential Rise(GPR) that may have a vital hazard for alives forms the basic of a safe grounding grid. In this paper, Genetic Algorithms(GA) method is proposed for the design of grounding grid on the structures of two-layer soil model and grid designs with and without grounding rods that are made by this method are compared. We have aimed both minimum cost and GPR is less than maximum allowable touch voltage on grounding grid designs. It is shown that grounding grid which are fast, cheap, easy, near to real, consistent and provides the safety conditions can be designed both with rods without rods by the way of purposed approach and the method. The role of grounding rods that carry out working safety conditions at grid designs is determined by cost analysis. Besides, the ground resistance that is measured on actual power system and the ground resistances that are calculated by uniform and two-layer soil models are compared. Keywords: Two-Layer soil model, grounding grid design, genetic algorithms, grounding potential rise, maximum allowable touch voltage, ground resistance.
Keywords: Two-Layer soil model; grounding grid design; genetic algorithms; grounding potential rise; maximum allowable touch voltage; ground resistance